Decrease in sodium intake and increase in dietary potassium: New physiological findings for a strategy for control and management of arterial hypertensión and cardiovascular risk - Rozas-Olivera, Víctor Vladimiro (2022)
During a short human evolutive period, there has been a marked increase in the oral intake of sodium and a reduction in the intake of potassium. In current urbanized societies the elevated oral intake of sodium has been linked to an increase in the prevalence of arterial hypertension and of the cardiovascular and cerebrovascular mortality. Recent investigations have also demonstrated sodium harmful effect over vital organs, independent of its action over blood pressure. In parallel, an increase in the oral potassium intake has shown an antihypertensive effect as well as antiinflammatory, anti-fibrotic and anti-oxidant effects. New physiological findings, along with epidemiological studies about the role of potassium in control of blood pressure, have stimulated the formulation of health policies towards a nutrition with less sodium and more potassium.